Interfacial transition zone between lignocellulosic fiber and matrix in cement-based composites - Santos, Sérgio Francisco [UNESP]; Teixeira, Ronaldo Soares; Savastano Junior, Holmer (Elsevier, 2017)
The objective of this chapter is to discuss some aspects that affect the interfacial transition zone between lignocellulosic fibers and cement matrix, such as raw materials, processing, and curing methods. A major advantage concerning fiber reinforcement of a brittle material is the composite behavior after cracking. Reinforcement is distributed into the composite leading to the effective capacity of reinforcing, which can be assessed through the pullout process and bridging cracks during the bending or direct tensile tests. According to the contributions of various research groups, the presence of fibrous reinforcement in the cement paste crucially depends on the interfacial transition zone between fibers and matrix. The understanding of the particle size distribution of the matrix constituents, nonuniformity and dimensional instability of lignocellulosic fibers, rheological properties of the cement paste in the fresh state, processing methods, and curing conditions adopted for the production of the composite materials, can help to improve durability and mechanical properties of these materials.
Keywords: Extrusion; Fiber surface chemistry; Interface frictional bond, accelerated carbonation curing; Particle size distribution; Rheology